Cultura de aprendizagem e desempenho organizacional no Instituto Nordeste Cidadania (INEC) - Arruda, Sérgio Chaves (2012)
The advancing innovation requires the organizations to incorporate new technologies and reformulate their management models with increasing speed. In this context, the phenomena of culture and organizational learning are being used to improve performance and promote the dynamism and flexibility necessary to make the organizational processes efficient and effective. The Non-governmental organizations (NGOs), are not out of the market that charge. For this reason, this research have the objective mains at analyze the relationship between learning culture and organizational performance in Instituto Nordeste Cidadania (INEC) with respect to financial performance and knowledge, supporting the perceptions of actors in different sectors of the organization. This study was based on the following hypotheses: H1: The culture of learning directly influences organizational performance in Instituto Nordeste Cidadania (INEC), in the perception of employees; H2: The learning culture factors that most influence on financial performance in Instituto Nordeste Cidadania (INEC), as perceived by employees, are the systems to capture and share learning and development of a systemic vision of the organization; H3: the learning culture factors that most influence the performance of knowledge in the Instituto Nordeste Cidadania (INEC), perceptions of employees, are opportunities for continuous learning and collaboration and team learning. The theoretical basis of this study are the factors defined by Marsick and Watkins (2003). Was used a quantitative methodology search of an explanatory nature. The questionnaire used was Dloq a (Yang, 2003), simplified version of the questionnaire developed by Marsick and Watkins (2003). The total number of participants this survey was 211, in which 77% of them are the State of Ceará. The results did not reject the hypotheses H1 and H2, H3 while partially rejected. The study indicates that the learning culture exerts significant influence on organizational performance in the Institute, the perception of its employees.